2018
DOI: 10.1017/s0007114518000934
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus absorption and gene expression levels of related transporters in the small intestine of broilers

Abstract: To investigate the P absorption and gene expression levels of related co-transporters, type IIb sodium-dependent phosphate co-transporter (NaPi-IIb), inorganic phosphate transporter 1 (PiT-1) and inorganic phosphate transporter 2 (PiT-2) in the small intestine of broilers, 450 1-d-old Arbor Acres male broilers were randomly allocated to one of three treatments with ten replicate cages of fifteen birds per cage for each treatment in a completely randomised design. Chickens were fed a diet with no added inorgani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…In addition, a post-transcriptional regulatory mechanisms including glycosylation or ubiquitination may be also involved in the NaP-IIb protein expression induced by P deficiency in this study (56) , but it needs to be investigated further. Hu et al (25) reported that a higher dietary NPP level promoted intestinal P absorption by increasing NaP-IIb protein expression, which was consistent with our results. Besides, dietary supplemental VD 3 enhanced NaP-IIb protein expression in the jejunum of the broilers fed the low NPP diets, suggesting that the increased absorption and utilisation of P induced by supplemental VD 3 might be partially associated with the enhanced NaP-IIb protein expression.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, a post-transcriptional regulatory mechanisms including glycosylation or ubiquitination may be also involved in the NaP-IIb protein expression induced by P deficiency in this study (56) , but it needs to be investigated further. Hu et al (25) reported that a higher dietary NPP level promoted intestinal P absorption by increasing NaP-IIb protein expression, which was consistent with our results. Besides, dietary supplemental VD 3 enhanced NaP-IIb protein expression in the jejunum of the broilers fed the low NPP diets, suggesting that the increased absorption and utilisation of P induced by supplemental VD 3 might be partially associated with the enhanced NaP-IIb protein expression.…”
Section: Discussionsupporting
confidence: 93%
“…The elevation of NaP-b expression levels in the E. faecium group may have resulted from increased available P in the intestine. The expression of NaP-b mRNA increases when the level of dietary P increases and is concentration dependent [41]. Some probiotics produce phytase [42], which would enhance phytate digestibility, releasing P for absorption.…”
Section: Discussionmentioning
confidence: 99%
“…After the blood sampling on day 42, the duodenum (about 10 cm distal to the pylorus), jejunum (about 10 cm preceding the Meckel's diverticulum) and ileum (about 10 cm preceding the ileocecal junction) were separated [21], and ushed gently with saline solution. The mucosa samples were scraped with a coverslip and snap-frozen in liquid nitrogen for analysis of mRNA.…”
Section: Experimental Designmentioning
confidence: 99%
“…Many studies have demonstrated that phosphate cotransporters were involved in P absorption of broilers (Fang, Xiang, Cao, & He, ; Hu et al, ; Liu et al, ). Therefore, the present study investigated the mRNA and protein expressions of NaP‐IIb, PiT‐1 and PiT‐2 in primary cultured duodenal epithelial cells of broiler embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on P absorption in half in vivo in situ ligated small intestinal loops of broilers indicated that the duodenum was the main site of P absorption, and P absorption was a saturable carrier‐mediated process in the duodenum but a non‐saturable diffusion process in the jejunum or ileum of broilers (Liu et al, ). Furthermore, our in vivo study demonstrated that the increase in dietary non‐phytate P levels inhibited NaP‐IIb mRNA level in the duodenum, but promoted NaP‐IIb protein level and PiT‐2 mRNA and protein levels in the duodenum of broilers (Hu et al, ). More recently, we and other researchers have successfully established the in vitro primary cultured duodenal epithelial cell model of 18‐d‐old chick embryos for studying P absorption (Lin, Jiang, Jiang, Zheng, & Gou, ; Zhang, Liao, Lu, Zhang, & Luo, ), but it remains unclear about the kinetics of P absorption and whether these phosphate cotransporters are involved in P absorption in primary cultured duodenal epithelial cells of chick embryos.…”
Section: Introductionmentioning
confidence: 91%